Conquiliometry of Neritina zebra of the Paradise beach in Mosqueiro, state of Pará, northern Brazil (March-May 2018) - Rayanne de Kássia Carvalho Salimos; Alessandra Silva de Assis; Taiana Amanda Fonseca dos Passos; Conceição de Nazareth de Oliveira Bezerra Madeiros; Mara Rúbia Ferreira Barros; Marko Herrmann (PANGAEA, 2019)
Samples were collected during the months of March, April, and May. Measuring the length (C), width (L), height (A), length of aperture (Ca) and width of aperture (La).